QASHQADARYO VILOYATI SUV OMBORLARINING SUV ZAHIRALARI VA ULARDAN UNUMLI FOYDALANISH MASALALARI - Suyarqulov, N.M. (SCIENCE and SOCIETY, 2024)
This article covers water resources of Kashkadarya region reservoirs and their future use. The article also talks about economic mechanisms of using regional water reservoirs and issues of water saving.
Keywords: reservoir; water resources; water saving; economic mechanisms; irrigation